The Analysis of Skilled Performance and Game Parameters During League Field Hockey Matches - Boddington, M. K.; Lambert, M. I.; Waldeck, M. R. (International Journal of Performance Analysis in Sport, 2003)
The performance profiles of field hockey were determined by quantifying match descriptors (n = 20) during league matches (n = 10). All data were analysed where appropriate, using Chi Square to determine if consistency within any of the match descriptors existed. Graphical methods were used to estimate consistency where there were low frequencies or Chi Square showed non-significant differences. Consistency was defined as minimum number of matches that could be analysed to establish a consistent profile. There were significant differences between 11 of the 20 match descriptors during the 10 matches (P<0.05). Normative or consistent profiles were established for 2 of the 20 match descriptors after only 1 match, and for 7 after 7 to 9 matches. The remaining 15 match descriptors did not profile before the 10th match. The ratio of shots to goals was stable after 2 games. Comparison of the matches against the same opposition in which the results differed, found significant differences in only 2 areas; the number of attacking short corners and the number of shots against. This suggests that more predictive comparisons can be made when the opponents are consistent. In conclusion, many match descriptors do not have stable profiles before 10 matches and are therefore of little use when trying to predict performance.